2020
DOI: 10.3389/fpls.2019.01681
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic Plasticity in Sexual Reproduction Based on Nutrients Supplied From Vegetative Ramets in a Leymus chinensis Population

Abstract: Phenotypic plasticity is considered a major mechanism that allows plants to adapt to heterogeneous environments. The physiological integration between the interconnected rhizomes or stolons of clonal plants influences the plasticity of such plants in heterogeneous environments. However, the determinants of plasticity of reproductive ramets in clonal plants in homogeneous environments are unclear. Here, we chose Leymus chinensis, a perennial rhizomatous grass, and conducted a series of field experiments in situ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 58 publications
(73 reference statements)
1
20
0
Order By: Relevance
“…H. glabra is a typical early spring grass, with its seed maturing in early June and approximately one and a half months earlier than L. chinensis . In the present study, in the natural populations of H. glabra , we found that vegetative ramets connected to tillering nodes could translocate their own resources to reproductive ramets through tillering nodes for seed production, which is highly consistent with the findings in L. chinensis [ 55 ]. This implies that there is an evident commonality between H. glabra and L. chinensis ; namely, during sexual reproduction, there is the physiological integration between different functional ramets connected by tillering nodes.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…H. glabra is a typical early spring grass, with its seed maturing in early June and approximately one and a half months earlier than L. chinensis . In the present study, in the natural populations of H. glabra , we found that vegetative ramets connected to tillering nodes could translocate their own resources to reproductive ramets through tillering nodes for seed production, which is highly consistent with the findings in L. chinensis [ 55 ]. This implies that there is an evident commonality between H. glabra and L. chinensis ; namely, during sexual reproduction, there is the physiological integration between different functional ramets connected by tillering nodes.…”
Section: Discussionsupporting
confidence: 90%
“…In this study, in the natural populations of H. glabra growing in relatively homogenous sandy soil ( Supplementary Table S7 ), we found that a reproductive ramet connected to two vegetative ramets had an average of 1.2 more seeds and 0.9% greater seed-setting rate than that connected to one vegetative ramet in 2018 ( Figure 1 A,C). In the same year, our research group investigated the sexual reproductive characteristics of L. chinensis growing in homogenous sandy soil in this study area and found that a reproductive ramet connected to two vegetative ramets had an average of 2.5 more seeds and 5.2% greater seed-setting rate than that connected to one vegetative ramet [ 55 ]. By this token, H. glabra had a lower capacity for physiological integration than L. chinensis .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mean annual precipitation ranges from 300 to 450 mm, more than 60% of which occurs from June to September. Mean annual temperature ranges from 4.6 to 6.4°C and the frost-free period lasts for 130 to 165 days (Guo et al, 2020). The soil is a mixed salt-alkali meadow steppe (Salid Aridisol, US Soil Taxonomy) with 29% sand, 40% silt and 31% clay (top 10 cm) (Zhu, 2004).…”
Section: Methodsmentioning
confidence: 99%
“…Tzvel. L. chinensis was selected as the study species for this experiment because it is a typical rhizome clonal plant, and is often exposed to grazing and mowing due to its good palatability for livestock [35,36]. Consequently, it is always subject to nutrient heterogeneity and herbivory-induced heterogeneity.…”
Section: Introductionmentioning
confidence: 99%